Ramp vs. step tests: valid alternatives to determine the maximal lactate steady-state intensity? - Caen, K.; Pogliaghi, S.; Lievens, M.; Vermeire, K.; Bourgois, J. G.; Boone, J. (European Journal of Applied Physiology, 2021)
Purpose: The aims of this study were (1) to investigate if the respiratory compensation point (RCP) as derived from ramp incremental (RI) exercise could accurately predict the power output (PO) at the maximal lactate steady state (MLSS), and (2) to compare its accuracy with the second lactate threshold (LT2) obtained from step incremental (SI) exercise. Methods: Nineteen participants performed a RI test (30 W·min-1) to determine RCP, a SI test (30 or 40 W·3 min-1) to determine LT2, and two or more constant work rate (CWR) tests to determine MLSS. For each participant, the V.O2/PO relationship for RI and CWR exercise was established. The ramp-identified PO at RCP was corrected by accounting for the gap between these relationships using the individually determined V.O2/PO regression above GET (RCPcorr-1) or using a fixed regression slope (RCPcorr-2). LT2 was determined using four methods: Dmax, modified Dmax (ModDmax), 4-mM threshold (LT4mM) and an expert-determined LT2 (LT2-expert). Results: RCPcorr-1 (235 ± 69 W), RCPcorr-2 (228 ± 58 W) and LT2-expert (227 ± 61 W) were not different from MLSS (225 ± 60 W). Dmax (203 ± 53 W) underestimated MLSS, while RCP (280 ± 60 W), ModDmax (235 ± 67 W) and LT4mM (234 ± 68 W) overestimated MLSS. The V.O2 at RCP (3.13 ± 0.79L·min-1) and LT2-expert (2.99 ± 0.19L·min-1) did not differ from MLSS (3.05 ± 0.72 L·min-1). Conclusion: This study demonstrated that RCP as derived from RI exercise and LT2 as derived from SI exercise can be equally accurate to determine the PO associated with MLSS. Although these results confirmed the suitability of RI and SI tests for this purpose, they also highlighted the importance of an appropriate threshold method selection and the eye of the expert.